Penerapan Prinsip Good Governance dalam Pengelolaan Anggaran Daerah: Systematic Literature Review - Firdaus Ro'mah; Irma Aliana Putri; Zowarni Azlina (Bussiness Academy of Lombok, 2026)
This study aims to analyze the application of good governance principles in regional budget management in Indonesia, which includes transparency, accountability, participation, effectiveness, efficiency, and the rule of law. The method used is a qualitative approach through a Systematic Literature Review (SLR) of scientific publications and policy documents from the 2018–2024 period. The results of the study show that the implementation of good governance in regional budget management is still not optimal, as indicated by limited transparency, weak accountability, low public participation, and weak law enforcement. This study is expected to serve as a basis for local governments to improve budget management to be more open, accountable, and responsive.